Determinants of Health and Disability in Ageing Population: The COURAGE in Europe Project (Collaborative Research on Ageing in Europe). (24th July 2013) - Leonardi, Matilde; Chatterji, Somnath; Koskinen, Seppo; Ayuso‐Mateos, Jose Luis; Haro, Josep Maria; Frisoni, Giovanni; Frattura, Lucilla; Martinuzzi, Andrea; Tobiasz‐Adamczyk, Beata; Gmurek, Michal; Serrano, Ramon; Finocchiaro, Carla; et al.
<x xml:space="preserve">Abstract</x> COURAGE in Europe was a 3‐year project involving 12 partners from four European countries and the World Health Organization. It was inspired by the pressing need to integrate international studies on disability and ageing in light of an innovative perspective based on a validated data‐collection protocol. COURAGE in Europe Project collected data on the determinants of health and disability in an ageing population, with specific tools for the evaluation of the role of the built environment and social networks on health, disability, quality of life and well‐being. The main survey was conducted by partners in Finland, Poland and Spain where the survey has been administered to a sample of 10 800 persons, which was completed in March 2012. The newly developed and validated COURAGE Protocol for Ageing Studies has proven to be a valid tool for collecting comparable data in ageing population, and the COURAGE in Europe Project has created valid and reliable scientific evidence, demonstrating cross‐country comparability, for disability and ageing research and policy development. It is therefore recommended that future studies exploring determinants of health and disability in ageing use the COURAGE‐derived methodology. Copyright © 2013 John Wiley & Sons, Ltd. Key Practitioner Message COURAGE in Europe Project collected data on the determinants of health and disability in an ageing population, with specific tools for the evaluation of the role of built environment and social networks on health, disability quality of life and well‐being. The COURAGE Protocol for Ageing Studies has proven to be a valid tool for collecting comparable data in the ageing population. The COURAGE in Europe Consortium recommends that future studies exploring determinants of health and disability in ageing use COURAGE‐derived methodology.